Euthanasia Controversy in Indonesia from The Perspective of Islamic Law - Nurdiah Lubis; Darania Anisa (PT. Global Pustaka Ilmiah, 2025)
The attempt to end the life of a person suffering from an incurable disease is called euthanasia. He will be relieved from suffering through the euthanasia process. This research aims to analyze the practice of euthanasia in the context of applicable law in Indonesia as well as reviewing its compatibility with the principles of Islamic law. This type of research is library research. The results show that in Indonesia, euthanasia is illegal and cannot be performed. Both positive law and the medical code of ethics prohibit euthanasia. According to Islamic law, active euthanasia is haram and can be punished by Allah with the punishment of hell for those who do it. The attempt to end the life of a person suffering from an incurable disease is called euthanasia. He will be relieved from suffering through the process of euthanasia. In Indonesia, euthanasia is illegal and cannot be performed. Both positive law and the medical code of ethics prohibit euthanasia. In Islamic law, it is explained that euthanasia.